MIMIKRI DAN RESISTENSI TOKOH JOHAN DALAM NOVEL TIDAK ADA ESOK KARYA MOCHTAR LUBIS - Ayuni, Adinda Mita; Setiadi, David; Suparman, Fauziah (Universitas Negeri Makassar, 2024)
This research aims to describe the analysis and characterization of Johan and the description of mimicry and resistance in the novel Tak Ada Esok Tomorrow by Mochtar Lubis. The method used in this research is the descriptive-qualitative method. The data in this research are sentences and quotations that contain characterization, mimicry, and resistance. Meanwhile, the data collection technique is reading and note-taking. Based on the results of the research, it shows the form of mimicry contained in the novel Tak Ada Esok by Mochtar Lubis, including mimicry of Japanese drunken culture, mimicry in dress, and the use of samurai weapons, namely katana. There is also a form of resistance by Johan and his troops in facing the Dutch-Japanese colonial period until the post-independence war.